Efeito da terapia fotodinâmica na quimiotaxia de macrófagos e linfócitos T ativados no tecido periodontal - Evangelista, Érika Elisabeth (2014)
Periodontal disease is an inflammatory disease affecting the supporting tissues of the teeth, leading to loss of periodontal ligament and bone. The treatment involves scaling and root planning, and in more advanced cases there is the need for surgery and sometimes antibiotics. Photodynamic therapy is a therapeutic antimicrobial resource to aid in modulation of the inflammatory response triggered by the light. One of the main cells is the macrophage inflammatory process which acts in reciprocity with T lymphocytes. Thus the aim of this study was to evaluate the effect of photodynamic therapy in the chemotaxis of macrophages and activated T lymphocytes in the periodontal tissue. For such, patients who have undergone previous periodontal treatment with good oral hygiene and periodontal pockets residual requiring surgery were allocated. PDT was applied on the following parameters: methylene blue (50ug / ml) was applied to the bottom of the pocket and after 5 minutes via transmucosal the photosensitizer was irradiated with diode laser 660 nm, P = 100 mW, t = 90 s per point 9 J/point; energy density: 22 J/cm2, power density: 250 mW/cm2. One week after PDT, the surgical removal of the pockets was performed and samples sent for routine histology and immunohistochemical detection of activated T lymphocytes (CD45RO +) and macrophages (CD68 +). The samples were photographed and positive cells counted with the aid of ImageJ software. Data were evaluated statistically and no significant difference between groups (Mann-Whitney p = 0.9). We conclude that PDT does not interfere with chemotaxis of macrophages and activated T lymphocytes in periodontal tissue after seven days.